#### Answer

$(g/f)(x)= \dfrac{x^2-5}{-2x+3}$

#### Work Step by Step

RECALL:
$(g/f)(x) = \dfrac{g(x)}{f(x)}$
Using the formula above gives:
$(g/f)(x) = \dfrac{g(x)}{f(x)}
\\(g/f)(x)= \dfrac{x^2-5}{-2x+3}$

Published by
Pearson

ISBN 10:
0-32184-874-8

ISBN 13:
978-0-32184-874-1

$(g/f)(x)= \dfrac{x^2-5}{-2x+3}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.